Corrosion of Sn-Ag-Cu lead-free solders and the corresponding effects on board level solder joint reliability - Fubin Song; Lee, S.W.R. (56th Electronic Components and Technology Conference 2006, 2006)
The drive for lead-free solders in the microelectronics industry presents some new reliability challenges. Sn-Ag-Cu alloys are leading candidates for lead-free solders. Compared to traditional Sn-Pb solders, Sn-Ag-Cu solders are easily corroded in corrosive environment due to their special structure. The presence of Ag 3 Sn in Sn-Ag-Cu solders accelerates the dissolution of tin from solder matrix into corrosive medium because of galvanic corrosion mechanism. When the corrosion present in the solder joints, it may change the microstructure of corroded regions and decreases the mechanical properties of solder joints by providing a crack initialization. In the present paper, the effects of salt spray test (based on JESD22-A107B) on the microstructure and mechanical properties of Sn-4.0%Ag-0.5%Cu solder balls are investigated with shear and ball pull test. The results show that the shear and pull strength of lead-free solder balls decreased after the slat spray test. In addition, three kinds of tests are performed to evaluate the effects of corrosion on the board level reliability of Sn-Ag-Cu solder joints, including drop test, three-point single strike and cyclic bending